2016
DOI: 10.1051/0004-6361/201527431
|View full text |Cite
|
Sign up to set email alerts
|

Quasar host environments: The view fromPlanck

Abstract: We measure the far-infrared emission of the general quasar (QSO) population using Planck observations of the Baryon Oscillation Spectroscopic Survey QSO sample. By applying multi-component matched multi-filters to the seven highest Planck frequencies, we extract the amplitudes of dust, synchrotron, and thermal Sunyaev-Zeldovich (SZ) signals for nearly 300 000 QSOs over the redshift range 0.1 < z < 5. We bin these individual low signal-to-noise measurements to obtain the mean emission properties of the QSO popu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 78 publications
4
32
5
Order By: Relevance
“…However, Cen & Safarzadeh (2015) argued that the observed thermal energies can be fully explained via gravitational heating alone, given the large beam sizes of a few arcmin for WMAP and Planck, and the uncertainties in the dust temperature in the calibration of the tSZ maps. More recently, Crichton et al (2016) performed tSZ analyses similar to those by Chatterjee et al and Ruan et al with a smaller-beam experiment (ACT, ∼ 1 arcmin; Swetz et al 2011) and also found a large thermal energy excess, consistent with the results by Dutta Chowdhury & Chatterjee (2017), although the importance of feedback still remains under debate because of the difficulties in analysing and interpreting the tSZ signal in all these analyses (Le Brun et al 2015;Verdier et al 2016;Hill et al 2017, see also the recent findings by Spacek et al 2017a). In detail, extracting conclusive information from the observations of the tSZ effect is difficult because the separation between the actual tSZ signal and that from other contaminants, i.e., thermal radiation from dust, requires a precise (not straightforward) modeling of the emission spectrum at various frequency bands (Cen & Safarzadeh 2015;Greco et al 2015;Ruan et al 2015).…”
Section: Introductionsupporting
confidence: 56%
“…However, Cen & Safarzadeh (2015) argued that the observed thermal energies can be fully explained via gravitational heating alone, given the large beam sizes of a few arcmin for WMAP and Planck, and the uncertainties in the dust temperature in the calibration of the tSZ maps. More recently, Crichton et al (2016) performed tSZ analyses similar to those by Chatterjee et al and Ruan et al with a smaller-beam experiment (ACT, ∼ 1 arcmin; Swetz et al 2011) and also found a large thermal energy excess, consistent with the results by Dutta Chowdhury & Chatterjee (2017), although the importance of feedback still remains under debate because of the difficulties in analysing and interpreting the tSZ signal in all these analyses (Le Brun et al 2015;Verdier et al 2016;Hill et al 2017, see also the recent findings by Spacek et al 2017a). In detail, extracting conclusive information from the observations of the tSZ effect is difficult because the separation between the actual tSZ signal and that from other contaminants, i.e., thermal radiation from dust, requires a precise (not straightforward) modeling of the emission spectrum at various frequency bands (Cen & Safarzadeh 2015;Greco et al 2015;Ruan et al 2015).…”
Section: Introductionsupporting
confidence: 56%
“…Testing this hypothesis requires observations at submillimetre (submm) wavelengths, as the copious amounts of dust generated from star-formation absorb the rest-frame optical and ultraviolet (UV) light emitted by stars and reradiate it in the far-infrared (IR), observed here on Earth in the submm due to the high redshifts (usually > 2) of these objects. For instance, one can compare the far-IR luminosities of SMGs and QSOs as a proxy of their total dust contents (e.g., Elbaz et al 2010;Hatziminaoglou et al 2010;Dai et al 2012;Leipski et al 2014;Verdier et al 2016). Observations of molecular gas lines (such as CO) in QSOs are also invaluable as they are associated with their host galaxies, allowing one to compare QSOs with their progenitor SMGs (Solomon & Vanden Bout 2005;Carilli et al 2007;Coppin et al 2008;Wang et al 2010;Simpson et al 2012); indeed, it is found that the molecular gas properties of local infrared QSOs, such as the molecular gas mass, star formation efficiency, and molecular linewidths are indistinguishable from those of ultraluminous infrared galaxies (e.g.…”
mentioning
confidence: 99%
“…However, there is no general consensus as the inferred thermal energies differ substantially among the various studies. One of the main obstacle in this analysis is represented by the strong dust signal which dominates the SED at ν 100 GHz (Crichton et al 2016;Verdier et al 2016;Soergel et al 2017) and creates a degeneracy with the tSZ signal. An additional complication involves distinguishing between the AGN-induced signal and that of the virialized gas in the host dark matter halo, see e.g.…”
Section: Future Outlookmentioning
confidence: 99%